Improving the Performance of Civil Servants and Daily-Contract Workers at the Satuan Polisi Pamong Praja of Batu City: The Role of Job Satisfaction and Work Motivation - Ilmawan, Mirza Dwinanda; Al Ichsan, Muhammad Rifky; Puspita, Nindi Vaulia (Fakultas Ekonomi Universitas Kadiri, 2025)
This research was conducted in the Batu City Civil Service Police Unit to contribute to the broader goal of improving public service quality by examining factors that influence employee performance. In Batu City, as in many other areas, local governments are actively seeking ways to enhance the effectiveness of their workforce. The research involved a quantitative approach with a sample of 94 individuals selected from a population of 124 through probability sampling. Data was collected using questionnaires. Statistical analyses included multiple linear regression, t-tests, F-test, and independent samples t-test. Both job satisfaction and work motivation significantly influenced the performance of civil servants and daily contract workers individually (t-test) and collectively (F-test). However, no performance differences were found between civil servants and daily contract workers.